Bacterial vaginosis: a review of approaches to treatment and prevention - Abbe, Carmen; Mitchell, Caroline M. (Frontiers in Reproductive Health, 2023)
Bacterial vaginosis (BV) is a common cause of vaginitis worldwide and is associated with serious reproductive health outcomes, including increased risk of preterm birth, sexually transmitted infections, and pelvic inflammatory disease. The current and only FDA-approved treatment regimens for BV are antibiotics, such as metronidazole and clindamycin. Antibiotics provide a short-term cure for bacterial vaginosis; however, fail to provide a consistent long-term cure for many women. Fifty to eighty percent of women experience a BV recurrence within a year of completing antibiotic treatment. This may be because after antibiotic treatment, beneficial strains of Lactobacillus, such as L. crispatus, do not recolonize the vagina. In the absence of an effective long-term cure, patients, providers, and researchers are exploring different approaches to treatment and prevention, resulting in a rapid evolution of perspectives on BV pathogenesis and approaches to management. Current areas of investigation for BV management include probiotics, vaginal microbiome transplantation, pH modulation, and biofilm disruption. Behavioral modifications that may help include smoking cessation, condom use and hormonal contraception. Additional strategies considered by many people include dietary modification, non-medical vaginally applied products, choice of lubricant, and treatments from medical practices outside of allopathic medicine. This review aims to provide a comprehensive and up to date outline of the landscape of ongoing and potential treatment and prevention strategies for BV.